Angiosarcoma of the scalp diagnosed by the presence of neck inflammation: a case report - Karube, Rei (Nature Publishing Group, 2012)
Angiosarcoma is an uncommon malignancy, which spread out from the endothelial cells of vessels. Scalp angiosarcoma with cervical lymph node metastasis is particularly rare. This article describes a rare case of angiosarcoma of the scalp, presenting as neck inflammation. Imaging procedures such as computed tomography (CT), magnetic resonance image (MRI) and ultrasonography (US) were not sufficient to diagnose this case. A needle biopsy provided an effective and accurate diagnosis of cervical lymph node metastasis. Additional observation and physical examination was required to diagnose the origin of the primary cancerous lesion. Once the angiosarcoma diagnosis was confirmed histologically, sequential weekly and monthly docetaxel (DTX) treatment was effective in preventing reoccurrence. Nonetheless, the optimization of angiosarcoma treatment remains a future goal. Although patients generally describe pain and swelling at the primary lesion site, this patient complained only of painful neck inflammation, without any indication of pain or swelling of the scalp. A revised diagnostic protocol should note that cervical lymph node metastasis of unknown primary origin may result from angiosarcoma of the scalp.